Banning Bribes Abroad: US Enforcement of the Foreign Corrupt Practices Act - Gutterman, Ellen (2015)
The United States has been at the forefront of international efforts to combat corruption in the global economy for almost forty years, chiefly through its Foreign Corrupt Practices Act [FCPA]. Over the past decade, US enforcement of the FCPA has surged in terms of both the number of enforcement actions and the application of increasingly expansive interpretations of jurisdiction through which to enforce the FCPA on an extraterritorial basis. Extraterritorial enforcement of the FCPA has promoted anti-corruption policies and the banning of bribes abroad, but three aspects of FCPA enforcement shape and constrain the broader goals of global anti-corruption governance in ways that limit effective governance practices and meaningful anti-corruption reform in the global economy: the narrow conception of corruption upon which the FCPA is based, the strategic trade frame that underlies the FCPA’s internationalization, and the legitimacy problems these suggest